Migration, ethnic relations and Chinese business - Chan, Kwok B. (Chinese worlds., 2005)
Incorporating research carried out over the last twenty years, this book documents the personal and collective responses of Chinese migrants and refugees to the prejudice and discrimination they have experienced. Using case studies of Chinese communities in Canada, Chan explores the different defence mechanisms Chinese migrants have created in order to escape the systemic and institutionalized discrimination they face. In particular, the book analyzes Chinese entrepreneurship, arguing that it is a collective response to blocked opportunities in host societies. Drawing upon emp.